Public Innovation Governance in Regional Data Integration: An Analysis of the Simata Policy in South Sumatra - Septriandi Setia Permana; Alfitri Alfitri; M. Husni Thamrin; Andries Lionardo; Ryan Adam (Green Publisher Indonesia, 2026)
Regional data integration is a crucial element in the digital transformation of bureaucracy, but its implementation is often faced with structural tensions between technical regulatory demands and strong sectoral egos. In South Sumatra Province, the One Data Information System (SIMATA) was initiated as a form of public innovation to break the information fragmentation impasse between Regional Apparatus Organizations (OPDs). This study aims to examine the implementation of SIMATA policies using the analytical framework of Public Innovation Governance. Through a qualitative method with a policy analysis approach, this study dissects strategic documents, regulatory instruments managed by the South Sumatra Provincial Diskominfo, and data governance practices at the regional level. The results of the analysis show that the effectiveness of SIMATA implementation is not solely determined by technological determination, but is highly dependent on the capacity of actor orchestration and administrative regularization. It was found that there is a contradiction between the formal data integration mandate and the institutional readiness of OPDs in the field. In this context, the Public Innovation Governance model serves as a bridging instrument capable of shifting passive bureaucratic compliance patterns into proactive network collaboration. This study concludes that the sustainability of SIMATA requires governance adaptation that goes beyond traditional hierarchical approaches, leading to a more adaptive innovation ecosystem. This study makes a theoretical contribution to the digital governance policy literature and offers practical recommendations for strengthening the One Data governance architecture at the local government level.